Highly conductive composite flame-retardant cable and preparation method thereof

CN122531837BActive Publication Date: 2026-10-16GUANGXI ACAD OF MARINE SCI (GUANGXI MANGROVE RES CENT) +2
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611025432.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-07-10
Publication Date
2026-10-16
Estimated Expiration
2046-07-10

AI Technical Summary

Technical Problem

[0005]本发明的技术方案中,设计云母带层和聚烯烃绝缘层作为导体的复合绝缘结构,能保证优良的电气性能,而且能很好的防潮、防振动;采用纵包氩弧焊轧纹金属带制成金属外护套,不仅接地保护灵敏可靠,同时具有优良的抗机械撞击的能力,有效防潮、防水,柔软性提高,改善弯曲不易的缺陷,减少敷设施工难度;在填充料中引入木质素纤维和乙酰化二淀粉磷酸酯协同改性氢氧化镁基矿物填充体系,能够抑制粉末现象,提升了材料的加工性以及矿物填充层的完整性,确保了电缆在火灾条件下的耐火稳定性

Benefits of technology

1. 本发明的高导电复合型阻燃线缆,优化了缆芯结构,通过在导体外表面设计云母带层和聚烯烃绝缘层作为导体的复合绝缘结构,能保证线缆优良的电气性能,而且能很好的防潮、防振动;同时优化矿物填充料的配方,综合提升了电缆的电气性能、阻燃性、机械性能及耐火完整性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122531837B_ABST
    Figure CN122531837B_ABST
Patent Text Reader

Abstract

The application relates to the technical field of electric wire and cable, and particularly discloses a high-conductivity composite flame-retardant cable and a preparation method thereof. The cable comprises, from inside to outside, a cable core, an armored layer, an inner sheath, a mineral filling layer and an outer sheath; the cable core comprises an insulating core, the insulating core comprises a copper conductor, a mica tape layer and a polyolefin insulating layer; the armored layer is a metal sheath made of longitudinally-wrapped argon arc welding corrugated aluminum tape; and the mineral filling material of the mineral filling layer comprises the following raw materials in parts by weight: magnesium hydroxide 20-30 parts, sodium silicate aqueous solution 8-15 parts, lignin fiber 1-3 parts and acetylated di-starch phosphate 0.5-2 parts. The high-conductivity composite flame-retardant cable optimizes the structure of the cable core, designs the mica tape layer and the polyolefin insulating layer as a composite insulating structure on the outer surface of the conductor, optimizes the formula of the mineral filling material, and comprehensively improves the electrical performance, flame retardancy, mechanical performance and fire resistance integrity of the cable.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of wire and cable technology, and in particular to a high-conductivity composite flame-retardant cable and its preparation method. Background Technology

[0002] With rapid economic and social development, urbanization is accelerating, buildings are becoming increasingly dense, and population density is significantly increasing. Under the influence of complex environmental factors, the safe operation of power systems faces severe challenges. Power accidents caused by cable lines due to overload, short circuits, and external fire sources occur frequently and can easily escalate into fires, causing serious casualties and property damage. In fire accidents, the insulation layer of ordinary cables (such as PVC insulated cables and cross-linked polyethylene insulated cables) decomposes and carbonizes rapidly when heated, resulting in a rapid loss of power supply capacity. This causes critical disaster relief equipment such as elevators, emergency lighting, automatic alarm systems, fire pumps, and smoke extraction systems to malfunction. Furthermore, cable fires have unique secondary hazards: when fire spreads along cable trays or shafts, it can cause control circuit failures, further escalating the accident; after the fire is extinguished, damaged main equipment is often difficult to repair, and the system cannot return to normal operation for a long time. Therefore, the flame retardancy and fire safety of wires and cables are receiving increasing attention from the industry and society, leading to more stringent requirements for the flame retardancy rating, fire resistance, and line integrity under fire conditions of cable products.

[0003] To address these issues, the industry has developed various types of fire-resistant cables. Among them, flexible mineral-insulated fire-resistant cables are widely used due to their excellent electrical performance, mechanical flexibility, and fire resistance. Most of these cables use only mica tape wrapping as insulation around the conductor, making them susceptible to moisture and affecting their electrical performance. Furthermore, these cables use mineral mud filler as a fire-resistant layer. Currently, commonly used mineral mud filler is primarily composed of magnesium hydroxide hydrate, supplemented with water glass in a specific ratio, and then extruded to form a continuous and dense fire-resistant layer. Under high-temperature fire conditions, magnesium hydroxide and other hydrates undergo an endothermic decomposition reaction, releasing water of crystallization, lowering the internal temperature of the cable, and simultaneously generating a fire-resistant magnesium oxide shell, providing heat insulation and oxygen barrier protection. However, existing mineral mud fillers (such as magnesium hydroxide and water glass systems) have many drawbacks in practical applications: the filler material is prone to powdering after extrusion, which leads to microscopic looseness or local defects inside the fireproof layer and reduces the fire resistance stability of the cable; secondly, this type of material is prone to moisture loss, which causes the fireproof material to solidify into a shell prematurely, which not only affects the mechanical properties of the cable, but also reduces its fire resistance. Summary of the Invention

[0004] To address the above shortcomings, this invention provides a high-conductivity composite flame-retardant cable that improves the cable's fire resistance and protective properties while ensuring its electrical performance. The specific technical solution is as follows: A high-conductivity composite flame-retardant cable comprises, from the inside out: a cable core, an armor layer, an inner sheath, a mineral-filled layer, and an outer sheath; the cable core includes several insulating cores, each insulating core comprising a copper conductor and a mica tape layer and a polyolefin insulation layer that sequentially cover the copper conductor from the inside out; the armor layer is a metal sheath made of longitudinally wrapped argon-arc welded corrugated aluminum tape; the mineral-filled layer comprises the following raw materials in parts by weight: 20-30 parts magnesium hydroxide, 8-15 parts sodium silicate aqueous solution, 1-3 parts lignin fiber, and 0.5-2 parts acetylated distarch phosphate.

[0005] In the technical solution of this invention, a composite insulation structure with a mica tape layer and a polyolefin insulation layer as conductors is designed to ensure excellent electrical performance and provide good moisture and vibration resistance. The metal outer sheath is made of longitudinally wrapped argon arc welded corrugated metal tape, which not only provides sensitive and reliable grounding protection, but also has excellent resistance to mechanical impact, effectively prevents moisture and water damage, improves flexibility, overcomes the defect of difficulty in bending, and reduces the difficulty of laying. The introduction of lignin fiber and acetylated distarch phosphate synergistic modification of magnesium hydroxide-based mineral filler system into the filler can suppress powdering, improve the processability of the material and the integrity of the mineral filler layer, and ensure the fire resistance stability of the cable under fire conditions.

[0006] Preferably, in the above-mentioned high-conductivity composite flame-retardant cable, the mica tape layer is made of multi-layer wrapped glass fiber film-reinforced synthetic mica tape, and the polyolefin insulation layer is made of irradiated cross-linked polyethylene insulation material. The insulation layer formed by overlapping and wrapping glass fiber-reinforced synthetic mica tape not only has high dielectric strength, high resistivity, and uniform dielectric constant, but also high heat resistance, improving the cable's temperature and fire resistance. The irradiated cross-linked polyethylene insulation material is extruded using ultraviolet irradiation cross-linking equipment. The irradiated cross-linked polyethylene insulation layer effectively protects the moisture resistance of the mica tape layer. Simultaneously, the tight wrapping of the mica tape eliminates the possibility of defects caused by vibration, maximizing the cable's fire safety, moisture resistance, and vibration resistance.

[0007] Preferably, in the above-mentioned high conductivity composite flame-retardant cable, the insulating cores are filled with filler rope, which is inorganic paper rope or flame-retardant PP rope, and after filling, it is wrapped with halogen-free low-smoke flame-retardant tape.

[0008] Preferably, in the above-mentioned high-conductivity composite flame-retardant cable, the outer sheath is made of low-smoke halogen-free flame-retardant polyolefin material, which reduces the emission of smoke and toxic gases during combustion while ensuring flame-retardant performance.

[0009] Preferably, in the above-mentioned high conductivity composite flame retardant cable, the mineral filling material of the mineral filling layer includes the following raw materials in parts by weight: 22-28 parts of magnesium hydroxide, 10-14 parts of sodium silicate aqueous solution (water glass, sodium silicate content is 40-50%, modulus is 2.8-3.2), 1.5-3 parts of lignin fiber, and 0.8-1.5 parts of acetylated distarch phosphate.

[0010] By introducing lignin fiber and acetylated distarch phosphate, the problems of easy water loss, solidification, and powdering in traditional mineral filler materials are effectively solved. Lignonin fiber, as a natural polymer material, has a porous structure and good moisture absorption and retention properties, which can delay the rapid evaporation of moisture. Acetylated distarch phosphate, as a modified starch, has excellent adhesion and film-forming properties, and a certain degree of water retention, which can inhibit the excessive migration of moisture. The combination of the two extends the workable time of the material (i.e., the construction window); improves the bonding force between magnesium hydroxide and sodium silicate particles, prevents volume shrinkage and microcrack propagation caused by moisture loss, and ensures the integrity of the mineral filler layer while maintaining good processability, thereby improving flame retardancy and fire resistance stability.

[0011] Preferably, in the above-mentioned high-conductivity composite flame-retardant cable, the low-smoke halogen-free flame-retardant polyolefin material comprises the following raw materials in parts by weight: 30-40 parts of ethylene-vinyl acetate copolymer (EVA), 6-15 parts of polyolefin elastomer (POE), 3-8 parts of linear low-density polyethylene (LLDPE), and 5-10 parts of composite flame retardant.

[0012] Preferably, in the above-mentioned high-conductivity composite flame-retardant cable, the composite flame retardant comprises the following raw materials in parts by weight: ammonium polyphosphate (degree of polymerization greater than 1000) 18-23 parts, zinc borate (2ZnO·3B2O3·3.5H2O) 6-9 parts, sodium lignosulfonate 3-7 parts, glycidyl etheroxypropyl cage-like polysilsesquioxane 0.1-0.3 parts, phytic acid solution (50% aqueous solution) 0.5-2 parts, and γ-aminopropyltriethoxysilane 0.1-0.3 parts. The composite flame retardant utilizes the synergistic effect between its components to significantly improve the flame retardant efficiency and thermal stability of the material.

[0013] Preferably, in the above-mentioned high-conductivity composite flame-retardant cable, the preparation method of the composite flame retardant includes the following steps: S1. Dissolve sodium lignosulfonate in deionized water at a weight ratio of 1:8~12, and adjust the pH to 4.0~5.0; add zinc borate, stir at 50~70°C for 1~3 h, and then add 0.05~0.1 parts of γ-aminopropyltriethoxysilane to obtain a lignin-zinc borate complex suspension; S2. Disperse ammonium polyphosphate in anhydrous ethanol at a mass ratio of 1:2~3, then add 0.05~0.2 parts of γ-aminopropyltriethoxysilane, stir at 40~60°C for 0.5~1 h, filter and dry to obtain modified ammonium polyphosphate; S3. While stirring, phytic acid solution is added dropwise to the lignin-zinc borate complex suspension obtained in step S1 to obtain suspension A; modified ammonium polyphosphate is dispersed in deionized water at a weight ratio of 1:5~8, then suspension A is added, stirred and mixed, and the temperature is raised to 50~70℃ for 0.5~1h. Lignin-zinc borate is deposited on the ammonium polyphosphate to form a lignin-zinc borate-phytic acid-ammonium polyphosphate complex, resulting in suspension B; S4. Add glycidyl etheroxypropyl cage-like polysilsesquioxane to suspension B and stir for 0.5~2h; then spray dry to obtain composite flame retardant.

[0014] In the above technical solution, sodium lignosulfonate and zinc borate are first mixed. The hydroxyl groups on the surface of zinc borate form borate ester bonds (BOC) with the phenolic hydroxyl groups of lignin. Then, γ-aminopropyltriethoxysilane is used for modification to obtain a lignin-zinc borate composite with amino groups on the surface. Phytic acid is then added. Phytic acid contains six phosphate groups and carries a negative charge. Through electrostatic adsorption, coordination chelation, hydrogen bonding, etc., a phytic acid-lignin-zinc borate ternary composite is formed with a negatively charged overall surface. This is then mixed with modified ammonium polyphosphate. The modified ammonium polyphosphate has -NH2 on its surface, which is protonated in the solution and becomes positively charged. Phytic acid-lignin-zinc borate is deposited on the surface of the ammonium polyphosphate. Finally, glycidyl etheroxypropyl cage-like polysilsesquioxane is used. Alkyl modification yields a composite flame retardant that prevents the flame retardant failure caused by water absorption and migration in polymer materials, thus avoiding impact on material surface quality. It forms a five-element synergistic flame retardant system of phosphorus, nitrogen, boron, zinc, and silicon, which forms a dense, thermally stable, expanding char layer during combustion, exhibiting excellent flame retardant and smoke suppression effects. Furthermore, modification with glycidyl etheroxypropyl cage-like polysilsesquioxane allows its epoxy groups to undergo ring-opening reactions with the amino and hydroxyl groups on the shell surface, grafting them onto the outermost layer of the flame retardant. This not only improves the compatibility of the composite flame retardant with polyolefin materials but also enhances the elongation at break and tensile strength of polyolefin materials when the cage-like structure of the glycidyl etheroxypropyl cage-like polysilsesquioxane is embedded in the polymer network.

[0015] Preferably, in the above-mentioned high-conductivity composite flame-retardant cable, the preparation of the low-smoke halogen-free flame-retardant polyolefin material includes: mixing ethylene-vinyl acetate copolymer, polyolefin elastomer, linear low-density polyethylene, and composite flame retardant, extruding and granulating to obtain the low-smoke halogen-free flame-retardant polyolefin material.

[0016] On the other hand, the present invention provides a method for preparing the above-mentioned highly conductive composite flame-retardant cable, comprising the following steps: (1) Anneal and draw copper rods into strands to form conductor cores; (2) Mica tape is wrapped around each conductor core, and insulation is extruded and irradiated to form an insulation layer to form an insulating core; (3) Multiple insulating cores are combined to form a cable core. The spaces between the insulating cores are filled with inorganic paper rope or flame-retardant PP rope. Then, halogen-free low-smoke flame-retardant tape is wrapped around the outside of the cable core. (4) A metal sheath is made by longitudinally wrapping argon arc welding of corrugated aluminum strip to obtain an armor layer; (5) An inner sheath is made by extruding polyolefin material onto the outer surface of the armor layer; (6) The mineral filler material is extruded and coated on the outer surface of the inner sheath, and then wrapped with halogen-free low-smoke flame-retardant tape to obtain the mineral filler layer; (7) A low-smoke, halogen-free flame-retardant polyolefin material is extruded onto the outer surface of the mineral filler layer to obtain an outer sheath.

[0017] Compared with the prior art, the beneficial effects of the present invention are: 1. The high conductivity composite flame-retardant cable of the present invention optimizes the core structure. By designing a mica tape layer and a polyolefin insulation layer on the outer surface of the conductor as a composite insulation structure, the cable can ensure excellent electrical performance and provide good moisture and vibration protection. At the same time, the formulation of the mineral filler is optimized, which comprehensively improves the electrical performance, flame retardancy, mechanical properties and fire resistance integrity of the cable.

[0018] 2. The high-conductivity composite flame-retardant cable of this invention, by adding lignin fiber and acetylated distarch phosphate to the mineral filling layer, works synergistically with sodium silicate aqueous solution to effectively delay the loss of moisture in the filling material. This avoids the pulverization caused by rapid moisture loss in traditional mineral mud fillers, improves processability, and extends the construction window. This mineral filling system can form a dense fire-resistant shell at high temperatures, improving fire resistance. Combined with the low-smoke halogen-free flame-retardant polyolefin material in the outer sheath, excellent heat insulation and oxygen barrier effects are achieved, ensuring the integrity of the line under fire conditions.

[0019] 3. The high-conductivity composite flame-retardant cable of the present invention has an outer sheath made of low-smoke halogen-free flame-retardant polyolefin material. A composite flame retardant is added to the polyolefin material. Through multi-component synergy, the composite flame retardant forms a dense expanded carbon layer and a ceramic protective layer during combustion, which has good flame-retardant and smoke-suppressing properties. At the same time, the composite flame retardant has good compatibility with the polyolefin material, can be evenly dispersed in the polyolefin material, and can also improve the mechanical properties of the polyolefin material, ensuring the long-term insulation stability of the cable, and has efficient, durable and safe flame-retardant protection. Attached Figure Description

[0020] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0021] Figure 1 This is a schematic diagram of the cross-sectional structure of the high conductivity composite flame-retardant cable of Embodiment 1 of the present invention; Figure 2 This is a flowchart of the preparation method of the high conductivity composite flame retardant cable of the present invention.

[0022] Main illustrations: 1-Copper conductor, 2-Mica tape layer, 3-Polyolefin insulation layer, 4-Filling rope, 5-Armor layer, 6-Inner sheath, 7-Mineral filling layer, 8-Outer sheath. Detailed Implementation

[0023] The specific embodiments of the present invention are described in detail below, but it should be understood that the scope of protection of the present invention is not limited to the specific embodiments. Unless otherwise defined, all technical terms used below have the same meaning as commonly understood by those skilled in the art. The technical terms used herein are for the purpose of describing specific embodiments only and are not intended to limit the scope of protection of the present invention. Unless otherwise specifically stated, all raw materials, reagents, instruments, and equipment used in the present invention are commercially available or can be prepared by existing methods.

[0024] Example 1 like Figure 1 As shown, this embodiment provides a high-conductivity composite flame-retardant cable, which includes, from the inside out: cable core, armor layer 5, inner sheath 6, mineral filling layer 7, and outer sheath 8.

[0025] Specifically, the cable core is the conductive core of the cable. The cable core includes several insulated cores, each consisting of a copper conductor 1 and a mica tape layer 2 and a polyolefin insulation layer 3 that sequentially cover the copper conductor 1 from the inside out. The copper conductor 1 serves as the conductive carrier, transmitting electrical energy. The conductor conforms to the first or second type of annealed copper conductor in GB / T3956-2008, and can be a tightly compressed round stranded conductor with a copper core, ensuring excellent high conductivity and low resistance loss.

[0026] The mica tape layer 2 and the polyolefin insulation layer 3 form a composite insulation structure. The mica tape layer is made of multi-layer wrapped glass fiber film reinforced synthetic mica tape as an inorganic mineral insulation layer. The polyolefin insulation layer 3 is made of irradiated cross-linked polyethylene insulation material and extruded using ultraviolet light irradiation cross-linking equipment. It can protect the mica tape layer 2. The composite insulation structure can not only ensure excellent electrical performance, but also provide good moisture and vibration protection.

[0027] Inside the cable core, the spaces between the insulating cores are filled with filler rope 4 to ensure the roundness and stability of the cable core structure. Inorganic paper rope or flame-retardant PP rope is used for filling. In this embodiment, inorganic paper rope is used. After filling, halogen-free low-smoke flame-retardant tape is wrapped around the core.

[0028] Specifically, armor layer 5 is a metal sheath made of longitudinally wrapped argon-arc welded corrugated aluminum strip. This metal sheath not only has excellent mechanical protection properties, resisting external mechanical stress, but also good shielding performance and waterproof sealing, effectively protecting the internal cable core from external environmental corrosion. Inner sheath 6 covers the outer surface of armor layer 5 and is made of low-smoke halogen-free cross-linked polyolefin material, serving as a transitional protection and buffer, preventing the mineral filler layer from directly contacting the metal sheath and causing corrosion, further improving the cable's safety and fire resistance. Mineral filler layer 7 is extruded onto the outer surface of inner sheath 6 and is a key layer for achieving high flame retardancy and fire resistance integrity.

[0029] The mineral filler material of the mineral filler layer 7 in this embodiment consists of the following raw materials in parts by weight: 25 parts magnesium hydroxide, 10 parts sodium silicate aqueous solution (sodium silicate content is 40%, modulus is 3), 2 parts lignin fiber, 1.5 parts acetylated distarch phosphate, and 1 part deionized water; the lignin fiber specifications are: cellulose content 75%, pH value approximately 7.5, loose density: 28.5 g / L, maximum fiber length 5 mm, average fiber length 1.1 mm, and specific surface area 2.6 m². 2 .

[0030] The preparation method of the mineral filler material includes: adding acetylated distarch phosphate to deionized water and mixing, then sequentially adding glass water, magnesium hydroxide, and lignin fiber, and mixing evenly in a mixer at a speed of 800 r / min for 20 min. The mineral filler material of this embodiment does not easily dry out or harden, has good extrusion processing performance, and does not exhibit pulverization.

[0031] Specifically, the outer sheath 8, as the outermost protective barrier, is made of low-smoke halogen-free flame-retardant polyolefin material. In this embodiment, it is commercially available halogen-free low-smoke flame-retardant thermoplastic polyolefin sheath material WDZ-Y-H90 orange, manufactured by CGN High-Tech Nuclear Materials (Guangdong) Co., Ltd.

[0032] This embodiment also provides a method for preparing a high-conductivity composite flame-retardant cable, such as... Figure 2As shown, the specific steps include: (1) Anneal and draw copper rods into strands to form conductor cores; (2) Mica tape is wrapped around each conductor core, and insulation extrusion and irradiation cross-linking insulation layer are performed to form an insulating core; First, two layers of glass fiber film reinforced synthetic mica tape are wrapped around the conductor core using a high-speed wrapping machine, with a mica tape layer thickness of 0.5 mm; Then, irradiation cross-linking equipment is used to extrude irradiated cross-linking polyethylene insulation material around the mica tape layer to form a composite insulation structure with a composite insulation structure thickness of 1.0 mm and the extrusion temperature is controlled between 160℃ and 170℃; (3) Multiple insulating cores are combined to form a cable core. Inorganic paper rope is filled in the gap between the insulating cores. After filling, halogen-free low-smoke flame-retardant tape is used for overlapping wrapping to tighten the cable core and prevent it from loosening. (4) Then, a metal sheath is made by longitudinally wrapping argon arc welding of corrugated aluminum strip to obtain the armor layer; specifically: select aluminum strip with a thickness of 1.0mm, wrap it longitudinally around the cable core through a forming mold to form a tubular structure; then, use argon arc welding technology to continuously weld the aluminum strip joint to form a sealed metal sheath. (5) Low-smoke halogen-free polyolefin material is selected as the raw material for the inner sheath and is uniformly extruded onto the outer side of the armor layer by an extruder; the extrusion temperature is set to 150℃~160℃ and the thickness of the inner sheath is controlled at about 1.0mm. (6) The mineral filler material is extruded and coated onto the outer surface of the inner sheath, and then wrapped with halogen-free low-smoke flame-retardant tape to obtain the mineral filler layer. Specifically, the prepared mineral filler material is put into a special mineral mud extruder, the extrusion temperature is controlled between room temperature and 40°C, the extruded mineral filler layer is tightly wrapped around the outer surface of the inner sheath, the thickness of the mineral filler layer is 3mm, and then immediately wrapped and fixed with halogen-free low-smoke flame-retardant tape; (7) Low-smoke halogen-free flame-retardant polyolefin material is extruded onto the outer surface of the mineral filler layer with a thickness of 2.0 mm. In order to obtain the outer sheath, the extrusion temperature is set to 160℃~170℃, and finally a high-conductivity composite flame-retardant cable is obtained.

[0033] Example 2 like Figure 1 As shown, this embodiment provides a high-conductivity composite flame-retardant cable, which includes, from the inside out: cable core, armor layer 5, inner sheath 6, mineral filling layer 7, and outer sheath 8.

[0034] Specifically, the cable core includes several insulating cores, each consisting of a copper conductor 1 and a mica tape layer 2 and a polyolefin insulating layer 3, which are sequentially wrapped around the copper conductor 1 from the inside out. The mica tape layer 2 and the polyolefin insulating layer 3 form a composite insulation structure. The mica tape layer is an inorganic mineral insulating layer made of multi-layered glass fiber film-reinforced synthetic mica tape, and the polyolefin insulating layer 3 is made of irradiated cross-linked polyethylene insulating material extruded using ultraviolet irradiation cross-linking equipment. Inside the cable core, filler ropes 4 are filled between the insulating cores. In this embodiment, inorganic paper ropes are used, and after filling, they are wrapped with halogen-free low-smoke flame-retardant tape.

[0035] Specifically, the armor layer 5 is a metal sheath made of longitudinally wrapped argon-arc welded corrugated aluminum strip. The inner sheath 6 covers the outer surface of the armor layer 5 and is made of low-smoke halogen-free cross-linked polyolefin material.

[0036] The copper conductor, irradiated cross-linked polyethylene insulation material, mica tape, halogen-free low-smoke flame-retardant tape, inorganic paper rope, aluminum tape, low-smoke halogen-free cross-linked polyolefin material, and mineral filler material in this embodiment are the same as in Embodiment 1.

[0037] The outer sheath 8 is made of low-smoke halogen-free flame-retardant polyolefin material. In this embodiment, the low-smoke halogen-free flame-retardant polyolefin material is self-made.

[0038] The low-smoke halogen-free flame-retardant polyolefin material is composed of the following raw materials in parts by weight: 35 parts ethylene-vinyl acetate copolymer (EVA), 12 parts polyolefin elastomer (POE), 6 parts linear low-density polyethylene (LLDPE), and 8 parts composite flame retardant. The preparation process of the low-smoke halogen-free flame-retardant polyolefin material includes: mixing the ethylene-vinyl acetate copolymer, polyolefin elastomer, linear low-density polyethylene, and composite flame retardant at 130℃ and 50 r / min for 20 min, followed by extrusion granulation to obtain the low-smoke halogen-free flame-retardant polyolefin material.

[0039] The composite flame retardant comprises the following raw materials in parts by weight: ammonium polyphosphate (degree of polymerization 1000) 20 parts, zinc borate (2ZnO·3B2O3·3.5H2O) 7 parts, sodium lignosulfonate 5 parts, glycidyl etheroxypropyl cage-like polysilsesquioxane 0.2 parts, phytic acid aqueous solution (mass solubility 50%) 1 part, and γ-aminopropyltriethoxysilane 0.2 parts.

[0040] The preparation method of the composite flame retardant includes the following steps: S1. Dissolve sodium lignosulfonate in deionized water at a weight ratio of 1:10 and adjust the pH to 4.5; add zinc borate and stir at 60°C for 2 hours at a stirring speed of 400 r / min; then add 0.1 parts of γ-aminopropyltriethoxysilane to obtain a lignin-zinc borate complex suspension. S2. Ammonium polyphosphate was dispersed in anhydrous ethanol at a mass ratio of 1:2, and then 0.1 parts of γ-aminopropyltriethoxysilane were added. The mixture was stirred at 50°C for 1 h at a stirring speed of 400 r / min, filtered, and dried to obtain modified ammonium polyphosphate. S3. Phytic acid aqueous solution is added dropwise to the lignin-zinc borate complex suspension obtained in step S1 while stirring, and the mixture is stirred to obtain suspension A; modified ammonium polyphosphate is dispersed in deionized water at a weight ratio of 1:5; then suspension A is added dropwise, stirred and mixed, and the temperature is raised to 60℃ and stirred for 0.5~1h at a stirring speed of 400r / min. Lignin-zinc borate is deposited on the ammonium polyphosphate to form a lignin-zinc borate-phytic acid-ammonium polyphosphate complex, resulting in suspension B; S4. Add glycidyl etheroxypropyl cage-like polysilsesquioxane to suspension B, stir at 60°C for 1 hour at a stirring speed of 400 r / min; spray dry to obtain composite flame retardant.

[0041] This embodiment also provides a method for preparing a high-conductivity composite flame-retardant cable, which includes the following steps: (1) Anneal and draw copper rods into strands to form conductor cores; (2) Mica tape is wrapped around each conductor core, and insulation extrusion and irradiation cross-linking insulation layer are performed to form an insulating core; First, two layers of glass fiber film reinforced synthetic mica tape are wrapped around the conductor core using a high-speed wrapping machine, with a mica tape layer thickness of 0.5 mm; Subsequently, irradiation cross-linking polyethylene insulating material is extruded around the mica tape layer using an extruder and ultraviolet irradiation cross-linking equipment to form a composite insulation structure with a composite insulation structure thickness of 1.0 mm, and the extrusion temperature is controlled between 160℃ and 170℃; (3) Multiple insulating cores are combined to form a cable core. Inorganic paper rope or flame-retardant PP rope is filled in the gap between the insulating cores. After filling, halogen-free low-smoke flame-retardant tape is used for overlapping wrapping to tighten the cable core and prevent it from loosening. (4) Then, a metal sheath is made by longitudinally wrapping argon arc welding of corrugated aluminum strip to obtain the armor layer; specifically: select aluminum strip with a thickness of 1.0mm, wrap it longitudinally around the cable core through a forming mold to form a tubular structure; then, use argon arc welding technology to continuously weld the aluminum strip joint to form a sealed metal sheath. (5) Low-smoke halogen-free polyolefin material is selected as the raw material for the inner sheath and is uniformly extruded onto the outer side of the armor layer by an extruder; the extrusion temperature is set to 150℃~160℃ and the thickness of the inner sheath is controlled at about 1.0mm. (6) The mineral filler material is extruded and coated onto the outer surface of the inner sheath, and then wrapped with halogen-free low-smoke flame-retardant tape to obtain the mineral filler layer. The prepared mineral filler material is put into a special mineral mud extruder, and the extrusion temperature is controlled between room temperature and 40°C. The extruded mineral filler layer tightly covers the outer surface of the inner sheath, and the thickness of the mineral filler layer is 3mm. Then, it is immediately wrapped and fixed with halogen-free low-smoke flame-retardant tape. (7) Low-smoke halogen-free flame-retardant polyolefin material is extruded onto the outer surface of the mineral filler layer with a thickness of 2.0 mm. In order to obtain the outer sheath, the extrusion temperature is set to 160℃~170℃, and finally a high-conductivity composite flame-retardant cable is obtained.

[0042] Comparative Example 1 This comparative example is the same as Example 1, except that the raw material of the mineral filling layer 7 does not contain lignin fiber and acetylated distarch phosphate, while the other components and their contents remain unchanged.

[0043] Comparative Example 2 This comparative example is the same as Example 1, except that the raw material of the mineral filling layer 7 does not contain lignin fiber, the weight of acetylated distarch phosphate is 3.5 parts, and the other components and contents remain unchanged.

[0044] Comparative Example 3 This comparative example is the same as Example 1, except that the raw material of the mineral filler layer 7 does not contain acetylated distarch phosphate, the weight of lignin fiber is 3.5 parts, and the other components and contents remain unchanged.

[0045] Comparative Example 4 This comparative example is the same as Example 2, except that the composite flame retardant is composed of the following raw materials in parts by weight: 20 parts ammonium polyphosphate (degree of polymerization 1000), 7 parts zinc borate, 5 parts sodium lignosulfonate, 0.2 parts glycidyl etheroxypropyl cage-like polysilsesquioxane, 1 part phytic acid aqueous solution (mass solubility 50%), and 0.2 parts γ-aminopropyltriethoxysilane. The composite flame retardant is prepared by the following method: sodium lignosulfonate is dissolved in deionized water at a weight ratio of 1:10, then zinc borate, γ-aminopropyltriethoxysilane, ammonium polyphosphate, phytic acid aqueous solution, and glycidyl etheroxypropyl cage-like polysilsesquioxane are added. The mixture is stirred at room temperature for 2 hours at a stirring speed of 400 r / min, and then spray-dried to obtain the composite flame retardant.

[0046] Comparative Example 5 This comparative example is the same as Example 2, except that 3-glycidoxypropyltrimethoxysilane is used instead of glycidoxypropylcage polysilsesquioxane in the composite flame retardant.

[0047] During the preparation of composite flame-retardant cables, mineral filler material was extruded and coated onto the outer surface of the inner sheath. The presence of pulverization was observed, and the results are shown in Table 1.

[0048] Table 1. Powdering phenomenon of mineral filler layer in Example 1 and Comparative Examples 1-4

[0049] As can be seen from the data in the table above, the mineral filler material of the present invention can suppress pulverization, which proves that the synergistic effect of lignin fiber and acetylated distarch phosphate can suppress pulverization.

[0050] Mechanical properties of the outer sheath materials of Examples 1-2 and Comparative Examples 4-5 were tested. The elongation at break and tensile strength were tested in accordance with the national standard GB / T2951.11-2008. The results are shown in Table 2.

[0051] Table 2. Properties of the outer sheath materials of Examples 1-2 and Comparative Examples 4-5

[0052] As shown in Table 2, the low-smoke halogen-free flame-retardant polyolefin material prepared by this invention has a similar tensile strength to commercially available low-smoke halogen-free flame-retardant polyolefin materials, but its elongation at break is superior. The tensile strength and elongation at break of the embodiments of this invention are significantly improved compared to the comparative examples, indicating that the preparation and component optimization of the composite flame retardant of this invention can improve the dispersibility of the composite flame retardant in polyolefin materials and improve the mechanical properties of low-smoke halogen-free flame-retardant polyolefin materials.

[0053] The cables prepared in Examples 1-2 and Comparative Examples 1-5 were subjected to fire resistance and flame retardancy tests. The fire resistance test was conducted according to the method in IEC 60331-1, with an ignition temperature of 830℃. The ignition times were sequentially set to 120 min, 125 min, 130 min, 135 min, and 140 min, with the longest ignition time (when the 2A fuse did not break and the indicator light did not extinguish) defined as the fire resistance time. The combustion test was conducted according to standard GB / T 18380.12, with an ignition time of 60 s. The char length was measured after cooling. The results are shown in Table 3.

[0054] Table 3 Fire resistance and flame retardant properties of each group of cables

[0055] A longer fire resistance time indicates better fire resistance, while a shorter charring length indicates better flame retardancy. Table 3 shows that, compared to Example 1 and Comparative Examples 1-3, the addition of lignin fiber and acetylated distarch phosphate to the mineral filler improves the fire resistance and flame retardancy of the cable. Comparing Example 2 and Comparative Examples 4-5, it can be seen that the addition of a composite flame retardant to the polyolefin material in this invention significantly improves the fire resistance and flame retardancy of the cable.

[0056] In summary, this invention, by incorporating lignin fiber and acetylated distarch phosphate into the mineral-filled layer, works synergistically with sodium silicate aqueous solution to ensure the integrity of the mineral-filled layer, thereby improving flame retardancy and fire resistance stability. Combined with the low-smoke halogen-free flame-retardant polyolefin material in the outer sheath, excellent heat insulation and oxygen barrier effects are achieved, ensuring the integrity of the wiring under fire conditions.

[0057] The foregoing description of specific exemplary embodiments of the invention is for illustrative and explanatory purposes. These descriptions are not intended to limit the invention to the precise forms disclosed, and it will be apparent that many changes and variations can be made in accordance with the foregoing teachings. The exemplary embodiments were chosen and described in order to explain the specific principles of the invention and its practical application, thereby enabling those skilled in the art to implement and utilize various different exemplary embodiments of the invention, as well as various different choices and variations.

Claims

1. A high-conductivity composite flame-retardant cable, characterized in that, From the inside out, the cable consists of: a cable core, an armor layer (5), an inner sheath (6), a mineral filling layer (7), and an outer sheath (8). The cable core includes several insulating cores, each consisting of a copper conductor (1) and a mica tape layer (2) and a polyolefin insulation layer (3) that sequentially cover the copper conductor from the inside out. The armor layer (5) is a metal sheath made of longitudinally wrapped argon-arc welded corrugated aluminum tape. The mineral filling material of the mineral filling layer (7) includes the following raw materials by weight: 20-30 parts magnesium hydroxide, 8-15 parts sodium silicate aqueous solution, 1-3 parts lignin fiber, and 0.5-2 parts acetylated distarch phosphate. The sodium silicate content is 40-50%; the outer sheath (8) is made of low-smoke halogen-free flame-retardant polyolefin material, which includes the following raw materials by weight: 30-40 parts of ethylene-vinyl acetate copolymer, 6-15 parts of polyolefin elastomer, 3-8 parts of linear low-density polyethylene, and 5-10 parts of composite flame retardant. The composite flame retardant includes the following raw materials by weight: 18-23 parts of ammonium polyphosphate, 6-9 parts of zinc borate, 3-7 parts of sodium lignosulfonate, 0.1-0.3 parts of glycidyl etheroxypropyl cage polysilsesquioxane, 0.5-2 parts of phytic acid solution, and 0.1-0.3 parts of γ-aminopropyltriethoxysilane.

2. The high conductivity composite flame-retardant cable according to claim 1, characterized in that, The mica tape layer (2) is made of multi-layer wrapped glass fiber film reinforced synthetic mica tape, and the polyolefin insulation layer (3) is made of irradiated cross-linked polyethylene insulation material.

3. The high conductivity composite flame-retardant cable according to claim 1, characterized in that, The insulating cores are filled with filler rope (4), which is an inorganic paper rope or a flame-retardant PP rope. After filling, it is wrapped with halogen-free low-smoke flame-retardant tape.

4. The high conductivity composite flame-retardant cable according to claim 1, characterized in that, The mineral filling material of the mineral filling layer (7) includes the following raw materials in parts by weight: 22-28 parts magnesium hydroxide, 10-14 parts sodium silicate aqueous solution, 1.5-3 parts lignin fiber, and 0.8-1.5 parts acetylated distarch phosphate.

5. The high-conductivity composite flame-retardant cable according to claim 1, characterized in that, The preparation method of the composite flame retardant includes the following steps: S1. Dissolve sodium lignosulfonate in deionized water at a weight ratio of 1:8~12, and adjust the pH to 4.0~5.0; add zinc borate, stir at 50~70°C for 1~3 h, and then add 0.05~0.1 parts of γ-aminopropyltriethoxysilane to obtain a lignin-zinc borate complex suspension; S2. Disperse ammonium polyphosphate in anhydrous ethanol at a mass ratio of 1:2~3, then add 0.05~0.2 parts of γ-aminopropyltriethoxysilane, stir at 40~60°C for 0.5~1 h, filter and dry to obtain modified ammonium polyphosphate; S3. Phytic acid solution is added dropwise to the lignin-zinc borate complex suspension obtained in step S1 while stirring and mixing to obtain suspension A; the modified ammonium polyphosphate is dispersed in deionized water, then added to suspension A, stirred and mixed, and heated to 50~70℃ for 0.5~1h. Lignin-zinc borate is deposited on the ammonium polyphosphate to form a lignin-zinc borate-phytic acid-ammonium polyphosphate complex, to obtain suspension B; S4. Add glycidyl etheroxypropyl cage-like polysilsesquioxane to suspension B and stir for 0.5~2h; then spray dry to obtain composite flame retardant.

6. The high conductivity composite flame-retardant cable according to claim 1, characterized in that, The preparation of the low-smoke halogen-free flame-retardant polyolefin material includes: mixing ethylene-vinyl acetate copolymer, polyolefin elastomer, linear low-density polyethylene, and composite flame retardant, followed by extrusion granulation to obtain the low-smoke halogen-free flame-retardant polyolefin material.

7. A method for preparing a high-conductivity composite flame-retardant cable as described in any one of claims 1 to 6, characterized in that, Includes the following steps: (1) Anneal and draw copper rods into strands to form conductor cores; (2) Mica tape is wrapped around each conductor core, and insulation is extruded and irradiated to form an insulation layer to form an insulating core; (3) Multiple insulating cores are combined to form a cable core. The spaces between the insulating cores are filled with inorganic paper rope or flame-retardant PP rope. Then, halogen-free low-smoke flame-retardant tape is wrapped around the outside of the cable core. (4) A metal sheath is made by longitudinally wrapping argon arc welding of corrugated aluminum strip to obtain an armor layer; (5) An inner sheath is made by extruding polyolefin material onto the outer surface of the armor layer; (6) The mineral filler material is extruded and coated on the outer surface of the inner sheath, and then wrapped with halogen-free low-smoke flame-retardant tape to obtain the mineral filler layer; (7) A low-smoke, halogen-free flame-retardant polyolefin material is extruded onto the outer surface of the mineral filler layer to obtain an outer sheath.

Citation Information

Patent Citations

  • Method for manufacturing wood fiber composite protective tube

    CN103625005A

  • Flexible fireproof cable and fireproof mud filler for same

    CN112071492A